The impact of digital technologies on the information potential of accounting (financial) statements. Part 1: the concept of assessing the information content of corporate reporting, the model of digitaliasation of assets, liabilities and their impact on the information potential of reporting - M. T. Turmanov; T. M. Rogulenko (Вестник университета)
The authors of the article analyzed the ability of digital technologies for managing financial assets and liabilities of corporate business entities to increase the information potential of their reporting. Starting points and landmarks of Russian and foreign standardized rules for the formation of various types of reporting and the conceptual apparatus of “digital” legislation were disclosed. The authors proposed a definition of the concept of “information potential of reporting”. The main factors for the growth of the information potential of reporting were revealed. The authors have identified contradictions in the characteristics of theorists and practitioners of the processes of digitalisation of financial assets and liabilities and their impact on the information potential of reporting. The influence of digital platforms and models on the completeness of the implementation of the principles of transparency in the formation of corporate reporting was determined. It was concluded that accounting and reporting standards are not adapted to the practice of tokenization of real assets. Research was carried out using general scientific methods of analysis and synthesis, as well as methods of logical comparison, reduction and selection of methodologically important facts of reality.